2018
DOI: 10.1002/cncr.31668
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between household income and patient‐reported symptom distress and quality of life in children with advanced cancer: A report from the PediQUEST study

Abstract: In this cohort of children with advanced cancer, children from low-income families were found to experience higher symptom burden and worse QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 37 publications
(81 reference statements)
3
74
0
Order By: Relevance
“…The null hypothesis for the t-tests was that there are no differences in the mean sociodemographic characteristics and natural environmental conditions (neighborhood greenery) between low and high-income neighborhoods. Block groups were categorized into low income and high-income neighborhoods based on whether the median income of a block group was greater than $50,000 [57]. The block groups with a median income less than $50,000 were coded as zero, representing low-income neighborhoods, and the rest were coded as one, representing high-income neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
“…The null hypothesis for the t-tests was that there are no differences in the mean sociodemographic characteristics and natural environmental conditions (neighborhood greenery) between low and high-income neighborhoods. Block groups were categorized into low income and high-income neighborhoods based on whether the median income of a block group was greater than $50,000 [57]. The block groups with a median income less than $50,000 were coded as zero, representing low-income neighborhoods, and the rest were coded as one, representing high-income neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
“…Physical symptoms were highly prevalent and distressful during the EOL period compared with psychosocial symptoms (Bell et al, 2010;Beretta et al, 2010;Birtar et al, 2015;Friedrichsdorf et al, 2014;Heath et al, 2010;Hechler et al, 2008;Ilowite et al, 2018;Rosenberg et al, 2016;Schindera et al, 2014;Theunissen et al, 2007;Tomlinson et al, 2011;Ullrich et al, 2010a;Ullrich et al, 2010b;Van Cleve et al, 2012;Wolfe et al, 2015). The most prevalent physical symptoms were fatigue, pain, poor appetite, and dyspnea followed by nausea, vomiting, constipation, and diarrhea.…”
Section: Symptom Prevalencementioning
confidence: 99%
“…Symptom Reporting. Parent proxy report (n = 13, 48%) was the most common method used to obtain information related to symptom experiences during the EOL period for children with cancer (Friedrichsdorf et al, 2014;Heath et al, 2010;Ilowite et al, 2018;Latha et al, 2016;Pritchard et al, 2008;Schindera et al, 2014;Theunissen et al, 2007;Tomlinson et al, 2011;Ullrich et al, 2010a;Ullrich et al, 2010b;von Lutzau et al, 2012;Wolfe et al, 2015;Zelcer et al, 2010) followed by medical chart review (n = 11, 41%; Bell et al, 2010;Beretta et al, 2010;Birtar et al, 2015;Hassan et al, 2018;Hechler et al, 2008;Hoell et al, 2017;Jagt-van Kampen et al, 2015;Kuhlen et al, 2016;Snaman et al, 2018;Veldhuijzen van Zanten et al, 2015;Ye et al, 2019). Of the studies that used parent proxy-report, 4 (31%) used a combination of parents', providers' and patients' reports (Ullrich et al, 2010a;Van Cleve et al, 2012;Wolfe et al, 2015;Zhukovsky et al, 2015).…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although considerable evidence exists regarding the presence of SES differences in health status and health care utilization globally [ 7 ], the evidence regarding SES inequalities within the context of EOL suffering remains fragmentary. Previous studies have reported that low SES cancer patients are more likely to experience higher mortality [ 8 13 ], depression [ 14 ] and other comorbidities [ 12 , 13 ], and greater symptom burden [ 15 ] compared to higher SES patients. Low SES cancer patients are also less likely to receive palliative care [ 16 , 17 ], and to die at home [ 17 ].…”
Section: Introductionmentioning
confidence: 99%